Hi everyone...

Im stuck on this question (and its xmas eve i dont want to be spending hours on this what appears to be a very simple problem....aaah! )

so in my lecture notes, i have the equation,

dy/dt = y+1/t-1 given the boundary condition y=1 at t=0

separating variables gives,

integral( dy/y+1) = integral (dt/y-1)

ln(y+1) = ln(t-1) + lnc - c

OR (now this is where im lost..how did they get c - bc and how on earth did c equal -2??? you'll see...)

y+1/t-1 = c - bc tells us that c = -2

y = 2(1-t)-1